Mechanical, fracture and thermal characterization of post-cured hybrid epoxy nanocomposites reinforced with Graphene nanoplatelets and h-Boron Nitride - Mantesh C. Choukimath Choukimath; N. R. Banapurmath; M. A. Umarfarooq (Fracture and Structural Integrity)
The post-curing process of cured composites is essential in enhancing the strength, stiffness, elevating the glass transition temperature, and reducing residual stress in polymer thermoset composites. The curing temperature and time are the key factors that affect these properties. In-situ polymerization method was used to prepare composites with varying weight percentages of graphene nanoplatelets (GNP) and hexagonal boron nitride (h-BN) nanofillers (0.1, 0.2, and 0.3 wt% GNP-based composites; 0.3, 0.4, and 0.5 wt% h-BN-based composites; 0.4, 0.5, and 0.6 wt% h-BN+GNP-based composites). The cured composites were post-cured at temperatures of 80C, 120C, and 160C for 120 minutes in a hot air oven. The presence of GNPs and h-BNs in the composites is confirmed using Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). Further mechanical and thermal properties were evaluated by conducting tensile, flexural, impact, fracture and differential scanning thermometry (DSC) tests. The simulation analyses were performed using Ansys software, and the results demonstrated a strong correlation with the experimental data, with discrepancies between the two consistently within a standard margin of 20%.